Reproductive health in women following abdominal organ transplant. Issue 5 (30th March 2018) - Sarkar, Monika; Bramham, Kate; Moritz, Michael J.; Coscia, Lisa
Abstract : Fertility is commonly impaired in women with end‐stage kidney and liver disease, although most women will have restoration of fertility within 1 year of transplant. Family planning is therefore critical to discuss with reproductive‐aged transplant recipients in the early posttransplant period, in order to ensure timely initiation of contraception, and optimal timing for conception. For women seeking pregnancy, the risks to the mother, graft, and baby should be discussed, including evaluation of immunosuppression safety and potential for adjusting medications prior to conception. With an increasing number of transplant patients now breastfeeding, immunosuppression safety in lactation continues to carry great importance. Abstract : The authors review reproductive health in women after abdominal organ transplant, including contraception, preconception, and pregnancy management.